Understanding the underlying mechanisms behind macrophage dysfunction in the elderly tumour microenvironment - Duong, Lelinh (Curtin University, 2023)
Cancer incidence increases with age which coincides with changes to immune cells, called macrophages. This thesis identified macrophages become dysregulated with ageing to promote tumour growth. Intracellular communication molecules, called mTOR, drive this process and targeting mTOR led to a significant decrease in tumour growth and enhanced survival amongst elderly hosts. These findings identify a therapeutic avenue to restore immune function and improve outcomes for elderly cancer patients.